Effectiveness of Augmented Reality in the Teaching of Health University Students: Quasi-Experimental Study - Rocío Martín-Valero; Alejandro Vega-Morales Sr; Francisco Javier Martín-Vega; Manuel Rodriguez-Huguet; Maria Carmen Rodríguez-Martínez; Maria Jesus Vinolo-Gil (JMIR Serious Games)
Abstract BackgroundThe exponential growth of new technologies has resulted in the need for updating the field of education. From the educational point of view, there are some studies that have promoted the implementation of new technologies. These facts have raised the need to implement augmented reality in the university environment, especially among students of health sciences. The use of augmented reality can mean a new approach to teaching by teachers and better learning by students. ObjectiveWe aimed to analyze the degree of usability of two augmented reality applications and to compare the academic performance between the control group and the experimental group at the Universities of Cádiz and Málaga. The students at the University of Málaga used the Zapworks augmented reality software, while those at the University of Cádiz used the Aumentaty augmented reality software for their respective experimental groups. The secondary objective was to measure the relationships between all the studied variables. MethodsThis was a quasi-experimental design with a posttest as the only evaluation measure. We followed the SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials) statement and the ethical and legal aspects of the Principles of the Declaration of Helsinki. An intervention was carried out using two augmented reality applications on the subject of General Procedures in Physiotherapy II at the Universities of Málaga and Cádiz. ResultsA total of 199 participants took part in the study. Demographic variables, ratings, and usability were assessed, followed by statistical analysis, with the results and their interpretation being described in the study. Significant differences (PPPPP ConclusionsSignificant differences were observed in those who used augmented reality compared to the control group, with higher values observed in the University of Cádiz. There are no correlations between the variables of usability and qualifications.